ANALISIS KOMPOSISI SERBUK KAYU KERUING (Dipterocarpus spp.) DAN AKASIA (ACACIA MANGIUM WILLD) TERHADAP KARAKTERISTIK BIOPELLET - Andi Prawoto; Muhammad Faisal Mahdie; Noor Mirad Sari (Universitas Lambung Mangkurat, 2019)
This research aims to analyze the influence of the composition of sawdust keruing (Dipterocarpus spp) and Acacia (Acacia mangium Willd) to the characteristics of biopellet which include moisture content, density, ash content, flying substance, bound carbon content and, calorific value. This research use the testing procedure American Standar Testing aand Material (ASTM) and the result obtained are compared with American Standar. The research results show the biopellet average moisture content ranged from 9.0794%-10.2907%, density values ranged from 0,508 g/cm³ - 0,599 g/cm³, the value of ash content ranged from 0,7233% - 1,2967%, the value of the flying substance ranged from 85.3400% - 87.73%, the value of the bound carbon content ranged from 1,2559% - 4,2840%, and the calorific value ranged from 4,318,58 cal/g - 4,594.66 cal/g. Parameters of moisture values, density values, flying values, and bound carbon values does not meet American standards. Parameters of ash values and calorific values meet American standards. The result of analysis of variance and further test showed that the difference of wood powder composition had no significant effect on the value of water content, ash content, flying agent value, bound carbon value and calorific value. But the real effect on the value of density.Keywords: Biopellet, Wood keruing, Acacia wood, Renewable energy